PENGARUH PEMBIAYAAN SYARIAH TERHADAP PENGUATAN MODAL UKM DI KOTA KENDARI - Sitti Zakiah Ma’Mun; Siti Maesaroh (Mega Aktiva, 2016)
Small and Medium Enterprises ( SMEs ) have a strategic role in economic development , on the other hand the inability of the SME sector in terms of capital constraints in increasing its production capabilities . Therefore the aim of this study wanted to determine the effect of strengthening the capital of Islamic finance to SMEs .The study site is located in the city of Kendari with a relatively small sample size ( 30 -50 ) are listed on the SME and SME Perindagkop Kendari . Sampling technique using a cluster sampling is sampling based on a predetermined area . with Islamic finance as the dependent variable and the capital structure of SMEs as an independent variable . Regression analysis is used as an analytical tool to determine the relationship and the influence of financing on the capital structure of SMEs , in order to improve the ability of capital ( capital gain ) . Results showed that the Syariah Financing affect the capital structure of SMEs in Kendari .